THE POSSIBILITY OF USING DATA MINING IN THE RESEARCH OF AGRICULTURAL HOLDINGS - Milunović, Milan; Damnjanović, Radovan; Imamović, Nedžad; Kostić, Radan; Ćurčić, Mihailo; Ristić, Vladimir; Bojanić, Dragan (Economics of Agriculture, 2018)
Purpose. The aim of this study was to examine the usefulness and accuracy of Data Mining techniques on the example of testing the presence of impact evaluation of the quality of the land on the level of income of agricultural holdings on the basis of test samples. Methodology. The study was analysis conducted on a random sample for identifying key factors in the research of impact evaluation of the quality of the land on the level of income of agricultural holdings, on a data set of 179 examples, where the input consists of various variables: factor of erosivity, the power of the land, reducing the pH value, presence of organic matter, then target discrete variables with two descriptive values: at a expected yield and real yield. Results and Conclusions. The results obtained from the experiments agree confirmed a physical and chemical factors properties largely determines the classification results.